Two Models of Early Weaning Decreases Bone Structure by Different Changes in Hormonal Regulation of Bone Metabolism in Neonate Rat - de Albuquerque Maia, L.; Lisboa, P. C.; de Oliveira, E.; da Silva Lima, N.; da Costa, C. A. S.; de Moura, E. G. (Hormone and Metabolic Research, 2013)
During the last decade a great concern has developed for determining what factors influence bone mineral accretion in healthy children. Mother’s milk represents the primary source of calcium and other nutrients in the neonate. The development of bone and adipose tissue has common origins. Since early weaning decreases adipogenesis in neonate, our aim was to evaluate bone metabolism in 2 models of early weaning (EW) in neonate rats. Lactating rats were separated into 3 groups: control: pups had free access to milk; MEW: dams were involved with a bandage mechanically (M) interrupting lactation in the last 3 days; and PEW: dams were pharmacologically (P) treated to block prolactin (0.5 mg bromocryptine/twice a day) 3 days before standard weaning. Significant difference had p<0.05. At weaning, MEW and PEW pups presented lower body weight ( − 18% and  − 15%), total body fat ( − 26% and  − 27%), total bone mineral density ( − 7% and  − 6%), total bone mineral content ( − 30% and  − 32%), bone area ( − 28% and  − 30%), serum osteocalcin ( − 20% and  − 55%), and higher C-terminal cross-linked telopeptide of type I collagen (CTX-I) (1.3 and 1.1-fold increase). However, serum ionized calcium was lower only in MEW pups ( − 34%), 25-hydroxyvitamin D was higher (1.4-fold increase), and PTH was lower ( − 26%) only in PEW group. The present study shows that both early weaning models leads to an impairment of osteogenesis associated with lower adipogenesis by different mechanisms, involving mainly changes in vitamin D and PTH.
Keywords: lactation; bone; early weaning; calcium; vitamin D; PTH